Genomic analysis detects polygenic sex determination and signs of early gonad differentiation in zebrafish - Liew, Woei Chang (2014)
Zebrafish is a popular research organism in many areas of developmental biology. However, knowledge on its sexual development is lacking. Before this project there were conflicting reports on zebrafish sex determination (SD) mechanism. There were reports that suggested zebrafish SD depended on environmental factors, while others claimed the presence of sex chromosomes. In addition to the confusion on SD mechanism, there was also a lack of information on when the bipotential gonad starts the testis or ovary differentiation process. This Ph.D. project aimed to address these two areas of zebrafish sexual development by using a combination of classical breeding and molecular methods.